Notaris sebagai Guardian of Legality dalam Ekosistem Investasi Digital dan Aset Kripto - Bintang, Dinantara Mega; Aminah, Aminah (Riwayat: Educational Journal of History and Humanities, 2025)
The development of digital investment and cryptocurrency in Indonesia requires adequate legal protection to ensure a safe, transparent, and trustworthy ecosystem. Notaries play a strategic role as guardians of legality, serving as parties that provide legal certainty, prevent dispute risks, facilitate regulatory compliance, and educate the public and digital industry actors on the legality of transactions. This study employs a literature review method, collecting, examining, and analyzing various secondary sources, including laws and regulations, scientific journals, legal articles, and publications related to digital investment and cryptocurrency. The findings indicate that notaries function not only as transaction recorders but also as mediators between regulations and digital practices, legal compliance enforcers, and educators of legal literacy for investors. The synergy among notaries, regulators, and digital platforms is a crucial factor in creating a legitimate and sustainable investment ecosystem. Moreover, the adaptation of notaries to digital technologies, including smart contracts and blockchain mechanisms, is key to enhancing legal protection for investors. These roles collectively affirm the notarys position as a primary pillar in maintaining the legality of digital transactions and strengthening the integrity of the cryptocurrency investment ecosystem in Indonesia.